POLA PENGELOMPOKAN VEGETASI MANGROVE DI TELUK PANGPANG TAMAN NASIONAL ALAS PURWO - , Lugi Hartanto, SP; , Dr. Erny Poedjirahajoe, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Mangrove ecosystem is a unique and vulnerable ecosystems and it has the role of multipurpose functions of both services biological, ecological and economical Pangpang mangrove forest in the bay is one characteristic of natural forests in the Alas Purwo National Park. Research on grouping patterns of mangrove vegetation in the Pangpang bay, Alas Purwo National Park is one of the necessary information that is given to managers to preserve mangrove forests. This study aims are to determine the composition of constituent species of mangrove forest vegetation in Pangpang bay, Alas Purwo National Park, to know the pattern of mangrove vegetation grouping formed in the Pangpang bay, Alas Purwo National Park, and to know the relationship among several factors such as salinity habitat, substrate thickness, soil pH, water pH and water temperature on the pattern of grouping of mangroves in the Pangpang bay, Alas Purwo National Park. This research is carried out in the Pangpang bay, Alas Purwo National Park with 198 hektars area, divided in 5 blocks with 15 lines of research observations. At each point it was made the 2 x 2 m observation plots for seedlings, 5 x 5 m for saplings and 10 x 10 m for the pole and tree. The using data analysis are vegetation analysis, analysis of two-dimensional ordination, and the relationship between the habitat factor clustering patterns were analyzed by simple correlation. The results show that the composition of the constituent species of mangrove vegetation to the level of the tree, pole and stake are 13 species, 14 species and 12 species which are dominated by Rhizophora apiculata Blume, whereas for Seedlings are found only 6 types dominated by species Ceriops tagal CB Rob. Clustering patterns of mangrove vegetation to the tree level consists of 4 groups, level pile consists of 4 groups of saplings to consist of 4 groups and Seedlings consists of 3 groups. Habitat factors are strongly associated with clustering patterns of mangroves include water temperature and salinity to the level of the tree, the water temperature to the level of the pole, the water temperature to the level of saplings and seedlings to levels closely related to the depth of mud and water temperature.